Deadly connections: States that sponsor terrorism - Byman, Daniel (Cambridge University, 2013)
Thousands of people have died at the hands of terrorist groups that rely on state support for their activities. Iran and Libya are well known as sponsors of terrorism, while other countries, some with strong connections to the West, have enabled terrorist activity by turning a blind eye. Daniel Byman's book is the first to analyze this phenomenon. Focusing primarily on sponsors from the Middle East and South Asia, it examines the different types of support that states provide, their motivations, and the impact of such sponsorship. The book also considers regimes that allow terrorists to raise money and recruit without providing active support. The experiences of Iran, Pakistan, Afghanistan, Syria, Saudi Arabia, and Libya are detailed here, alongside the histories of radical groups such as al-Qa'ida, Hizballah, and HAMAS. In conclusion, the book also assesses the difficulties of forcing sponsors to cut ties to terrorist groups.